A further contribution to the knowledge of Pectiniunguis minutus (Demange, 1968), a little known dwarf schendylid centipede from western equatorial Africa (Chilopoda: Geophilomorpha) - Pereira, Luis Alberto (2011)
The geophilomorph centipede Pectiniunguis minutus (Demange, 1968), a little known dwarf schendylid from Gabon (Western equatorial Africa), is redescribed and illustrated based on the type material and an additional non-type specimen preserved in the collections of the Muséum national d'Histoire naturelle, Paris. P. minutus can be easily differentiated from all the other species currently assigned to the genus Pectiniunguis, by the very low number of leg-bearing segments (35 in the males, 37 or 39 in the females) and very small body size (12-16 mm in length). P. minutus is also distinguished by having ventral pore-fields on the anterior region of the body only, this character being shared by a single species of the genus, i.e., P. ascendens Pereira, Minelli & Barbieri, 1994, from the Neotropics (Brazil: State of Amazonas) with which a morphological comparison is given. Comments about other dwarf centipede species belonging to several families of the order Geophilomorpha, are also added.